Penegakan Hukum Pidana terhadap Pelanggaran Hak Pekerja: Studi Kasus Penelantaran Buruh Berdasarkan Undang-Undang Nomor 13 Tahun 2003 (International Forum of Researchers and Lecturers, 2025)
This study uses a qualitative method to analyze criminal law enforcement against violations of workers’ rights, especially cases of worker neglect based on Law Number 13 of 2003 concerning Manpower. The focus of this study is to examine how the implementation of criminal law is applied in handling cases of worker neglect, as well as the effectiveness of legal protection provided to workers whose rights are violated. Through a descriptive analytical approach, data were collected from various sources, including interviews with related parties and legal document studies, in order to obtain a comprehensive picture of the obstacles and challenges in law enforcement in the field of employment. The results of the study indicate that although Law Number 13 of 2003 has clearly regulated the rights and obligations of workers and employers, there are still obstacles in its implementation, especially in terms of supervision and enforcement of criminal sanctions against violations. This study recommends increasing the role of labor inspectors and optimizing law enforcement mechanisms to ensure effective protection of workers’ rights.